Al-'Urf Theory and Its Relevance to Contemporary Jurisprudence Issues - Andriyaldi Andriyaldi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
One of the syar'i arguments in the study of ushūl fiqh is the al-’urf argument. In classical ushūl fiqh books, the argument of al-’urf tends not to be a special discussion chapter, but it is included in various studies of ushūl fiqh when a mujtahid performs legal istinbāth. It means that al-’urf becomes an external determining factor in the legal istinbāth process. Therefore a mujtahid, as required by Imam Syatibi, must master two sets of ijtihad; (1) Understanding and mastering the arguments (fiqh al-nash), and (2) Understanding the conditions under which the texts or propositions will be applied (fiqh al-wāqi'). The study of al-’urf is closely related to the second point: understanding the situation and conditions when doing legal istinbāth. It is where the urgency of the argument of al-’urf in the legal istinbāth process is seen. This study found that: (a) For the law to be established to find its purpose and benefit, a mujtahid must consider the al-’urf argument as a proposition from outside the existing text (nash) or as accompanying arguments for other arguments. (b) In subsequent developments (modern era), legal changes are not only determined by changes in conditions (al-ahwāl), times (al-azminah) and places (al-amkinah), but in subsequent developments also triggered by other changes. such as changes in the information, changes in the level of human need for certain objects, changes in the level of human abilities, changes in the matter of 'general al-balwā (inevitable needs). All of these are factors other than those that are generally recognized. (c) New (contemporary) problems that arise due to the development of science and technology (science) require a mujtahid to understand the various new problems that exist, especially in the fields of medical, economic and technological progress. By understanding the various changes and changes in the situation, condition, and place, it is hoped that the new laws are required to find their purpose (benefit) and wisdom. All of the problems in this research are examined with a library research approach while contextualizing new contemporary issues. Salah satu dalil syar’i dalam kajian ushūl fikih adalah dalil al-’urf. Dalam buku-buku ushūl fikih klasik, dalil al-’urf cenderung tidak menjadi bab pembahasan khusus, namun ia masuk dalam berbagai kajian ushūl fikih ketika seorang mujtahid melakukan istinbāth hukum. Artinya al-’urf menjadi faktor eksternal penentu dalam proses istinbāth hukum. Karena itu seorang mujtahid, sebagaimana disyaratakan Imam Syatibi, harus menguasai dua perangkat ijtihad; (1) Memahami dan menguasai dalil (fiqh al-nash), dan (2) Memahami situasi kondisi dimana nash atau dalil akan diterapkan (fiqh al-waqi’). Kajian al-’urf sangat berkaitan dengan poin kedua, yaitu memahami situasi dan kondisi ketika melakukan istinbāth hukum. Disinilah, terlihat urgensi dalil al-’urf dalam proses istinbāth hukum. Dari rumusan-rumusan masalah yang dikemukakan, maka ditemukan kesimpulan penelitian ini sebagai berikut: (a) Agar hukum yang ditetapkan menemukan tujuan dan kemaslahatannya, maka seorang mujtahid harus mempertimbangkan dalil al-’urf sebagai dalil dari luar teks (nash) yang ada atau sebagai dalil pendamping bagi dalil-dalil lainnya. (b) Dalam perkembangan selanjutnya (era modern) perubahan hukum tidak saja ditentukan oleh perubahan kondisi (al-ahwāl), zaman (al-azminah) dan tempat (al-amkinah)saja, namun pada perkembangan selanjutnya juga dipicu oleh perubahan-perubahan lainnya seperti perubahan informasi, perubahan tingkat kebutuhan manusia terhadap objek tertentu, perubahan kadar kemampuan manusia, perubahan dalam soal ‘umum al-balwa (kebutuhan yang tak terelakkan). Semua ini adalah faktor-faktor lain diluar faktor-faktor yang umumnya dikenal. (c) Persoalan-persoalan baru (kontemporer) yang muncul karena perkembangan sains dan teknologi (ilmu pengetahuan) mengharuskan seorang mujtahid untuk memahami berbagai persoalan baru yang ada terutama dalam bidang kemajuan kedokteran, ekonomi dan teknologi. Dengan memahami berbagai perubahan, disamping perubahan situasi, kondisi dan tempat, maka diharapkan hukum-hukum baru yang diistinbāthkan menemukan tujuan (kemaslahatan) dan hikmahnya. Semua persoalan yang ada dalam penelitian ini dikaji dengan pendekatan kajian kepustakaan (library research) sembari melakukan kontekstual terhadap persoalan-persoalan baru kontemporer.